Non-Verbal Communication and Cues in Armenian-American Literary Discourse - Khachibabyan, Mane (Տիգրան Մեծ)
Communication is foundation of life. Literature is a universal form of communication. Writers communicate beliefs, ideas, experiences, feelings and thoughts. Armenian-American literature is a huge source of communication. Armenian-American writers who migrated to the USA throughout various time periods bring unique storylines and techniques to literature. Nonverbal communication is known to be the more honest part of human communication. Understanding communication requires combined analysis of verbal and nonverbal communication. This research identifies features of nonverbal communication incorporated in literary texts. Nonverbal cues incorporated in literary texts are seemingly minor yet vital features which sometimes are left out of the readers’ attention. The following literary works were chosen for the research: Peter Balakian’s Black Dog of Fate (1997, memoir), Micheline Aharonian Marcom’s Three Apples Fell from Heaven (2001, fiction). The chosen samples include writings which have not been widely analysed especially from communication theory aspects. The main analysis method utilized was close reading of the texts. Further, research can be done to analyse poetry collections to identify whether nonverbal cues are as significantly used in poetry as they are used in stories and novels.
Keywords: Literature; Armenian-American writers